Critical analysis on destination image literature: roles and purposes - Abdul Rashid, Rosmalina; Ismail, Hairul Nizam (2008)

(untitled)
A tourism destination is reviewed as an amalgamation of places that generating not just experiences, but provide a memorable destination experience to the tourists. The challenge for today’s tourism marketers is that tourists have to be enticed since the tourism destination is an intensely competitive and many destination competing with one and another to attract the similar segment of potential tourists, or repeated visitor. Thus, image of the destination is vital to develop appropriate marketing strategy and being used as promotional tools, not only to the operator of the business but also to those responsible in tourism development. In this case, the role of image has been shown to be an important factor in influencing tourists’ preferences and selection of vacation destinations. Therefore, this paper attempt to review the pertinent of previous literatures on destination image and the specific variables that has been examined in those literatures. Fundamentally, the paper will focusing the process involve before visitor making a visit, during and after the visitation, as well as the next process in making the second visit to the similar destination. The dominant subject that emerged from the research articles are critically analyzed the implications for destination image management and research.